1989
DOI: 10.1021/bi00444a013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 monocarboxylic acids: unambiguous isomer assignments by modern two-dimensional NMR spectroscopy

Abstract: The three cyanocobalaminmonocarboxylic acid isomers known to be produced by the mild acid hydrolysis of the b-, d-, and e-propionamide side chains of vitamin B12 have been unambiguously assigned by modern 2D NMR methods. Previously, structural assignments had been made by less definitive NMR methods, and both X-ray and neutron diffraction studies had failed to locate unambiguously the position of the carboxyl group. The b and e isomers were structurally assigned in this study, on the basis of the assignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Mild acid hydrolysis of (CN)Cbl ( 1 a ) leads to a mixture of the corresponding monocarboxylic acids 13 a ‐ c at the b , d , e‐ positions, respectively, along with di‐ and tricarboxylic derivatives (Scheme ) ,. Although yields are far from satisfactory and the purification process remains laborious, the access to monoacids 13 has opened new vistas for tethering cargoes at the periphery of the macrocycle.…”
Section: Conjugation At the Macrocyclic Corementioning
confidence: 99%
“…Mild acid hydrolysis of (CN)Cbl ( 1 a ) leads to a mixture of the corresponding monocarboxylic acids 13 a ‐ c at the b , d , e‐ positions, respectively, along with di‐ and tricarboxylic derivatives (Scheme ) ,. Although yields are far from satisfactory and the purification process remains laborious, the access to monoacids 13 has opened new vistas for tethering cargoes at the periphery of the macrocycle.…”
Section: Conjugation At the Macrocyclic Corementioning
confidence: 99%
“…[26,28] Subsequent neutron diffraction studies indicated that it could be the bacid, an assumption that was later confirmed by sophisticated multi-dimensional NMR measurements. [29][30][31][32] The similar diffraction power of the OH and NH 2 groups was the problem in X-ray analysis. Cobalamin crystals were rarely obtained in the quality required for an unambiguous differentiation between these two groups.…”
Section: Synthesesmentioning
confidence: 99%
“…However, previous in-vestigators have shown that NMR could be used to distinguish the isomers (58,59). Assignments were still somewhat ambiguous until an elaborate set of NMR experiments were conducted to assign all of the 1 H and 13 C resonances of two of the three isomers (b-and e-; dwas insoluble in adequate quantities for the experiment), and those assignments were used to correlate their connectivities in two-dimensional NMR spectroscopy with structures (60). That study unambiguously assigned structures to all three isomers (d-isomer by default).…”
Section: Preparation Of Corrin Ring B- D- and E-carboxylate Conjugate...mentioning
confidence: 99%